MEMUTUS RANTAI KEKERASAN TERHADAP PEREMPUAN MELALUI SOSIALISASI RELASI GENDER HARMONI PADA SISWA SMAN 8 JAKARTA - Syarief Darmoyo; Maria Tri Warmiyati; Sri Hapsari Wijayanti (LPPM UPN Veteran Jakarta, 2018)
Abstract The National Commission on Violence Against Women (Komnas Perempuan) notes that the level of violence against women has been so massive throughout 2017. The violence mostly occurs in the private sphere and is in the form of physical violence, sexual violence and courtship violence, and is mostly carried out by the closest victims namely boyfriend. Violence against women can occur because of the imbalance of power in gender relations. To break the chain of violence against women, this training aims to foster awareness about the values of gender equality in gender harmony relations among students of SMAN 8 Jakarta. This training uses an active student learning approach that requires participants to actively participate in the learning process. For this reason, various learning methods were chosen, among others: the lecture method, question and answer, group discussion, and watching together the film LOVE (Story of Violence in Dating). The training participants consisted of 170 class X students of SMAN 8 Jakarta. To evaluate the effectiveness of training, this training uses qualitative data collection methods namely observation and interviews, and thematic analysis is used as a data analysis technique. Evaluation results indicate that this training is effective. This can be seen from the increasing insight and awareness of students about the values of gender equality as they view women as having the same position as men in family and society, seeing gender is not God's nature, can recognize forms of violence: physical violence, psychological, sexual, and economic, and being negative about violence in courtship.